Molecular Detection and Phylogenetic Analysis of Canine Parvovirus-2 in Dogs - Khadse, Monali Bhagwan; Rambhau, Shubhangi; Kolangath, Sujit (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Canine Parvovirus (CPV) is a most significant viral disease causing acute haemorrhagic gastroenteritis and myocarditis in puppies at the age of 3-4 months. It causes serious morbidity and mortality, in spite of the effective vaccination. Inadequate immunity and modern practices of early weaning in the kennels have predisposed the young dogs to CPV.  In the present study, total 50 fecal samples were collected from dogs suspected for CPV-2 from Nagpur, India and screened by Ubioquick® VET lateral flow assay kit and Polymerase Chain Reaction (PCR) followed by the sequencing and phylogenetic analysis of VP2 gene. Out of 50 samples, 10 (20%) were found positive by antigen detection test, 18 (36%) by Conventional PCR method. Sequence analysis revealed 98-99% homology with sequences of CPV-2b antigenic type reported in dogs from India and Srilanka.
Keywords: Canine Parvovirus; Antigen Detection Test; Polymerase Chain Reaction (PCR); Sequencing and Phylogeny